Depressive Symptoms, Help-Seeking, and Barriers to Mental Healthcare Among Healthcare Professionals in Lithuania - Rogoža, Daniel; Strumila, Robertas; Klivickaitė, Eglė; Diržius, Edgaras; Čėnaitė, Neringa (Acta medica Lituanica, 2021)
Background: Previous research suggests that healthcare professionals (HCPs) experience high levels of work-related psychological distress, including depressive symptoms. Due to the stigma of mental health problems and other barriers, HCPs are likely to be hesitant to seek appropriate mental healthcare. We aimed to explore these phenomena among HCPs in Lithuania. Methods: A web survey inquiring about depressive symptoms, help-seeking, and barriers to mental healthcare was conducted. Depressive symptoms were measured using the Patient Health Questionnaire-9 (PHQ-9). 601 complete questionnaires were included in the analyses. The barriers to help-seeking were identified using the inductive content analysis approach. Descriptive, non-parametric, and robust statistical analysis was performed using SPSS software. Results: Most of the respondents have reported depression-like symptoms over the lifetime, although only about a third of them sought professional help. Of those, roughly half preferred a private specialist. The stigma and neglect of mental health problems were the most common barriers to help-seeking. Around half of the HCPs believed that seeking mental healthcare can imperil their occupational license. About a quarter of the HCPs screened positive for clinically relevant depressive symptoms. Statistically significant differences in the PHQ-9 score were found between categories of healthcare specialty, marital status, religious beliefs, workplace, and years of work as a HCP. Fewer years of work and younger age were associated with the higher PHQ-9 score. Conclusions: Our findings suggest that HCPs in Lithuania may be inclined not to seek appropriate mental healthcare and experience poor mental health, although stronger evidence is needed to verify these findings.